Efficiency shooting program for youth basketball players - Zambova, D.; Tomanek, L. (SportLogia, 2012)
Shooting practice in youth basketball is "cornerstone" for proper shooting technique, likely, enabling the player to get high shooting percentage in a Professional League (adults). The purpose of this study was to verify the efficiency of the shooting fundamental program (n = 18, age 9.85 ± .53). Experimental groups were used in these results. The results showed the effect of shooting fundamental program. Shooting test the lay-ups after this period of an experiment was increased by +1.83 successful attempts in comparison with the result in the control time (+1.45) (p < .01). These findings show that efficiency of basketball shooting fundamental program increase shooting percentage during the period of an experiment.